2007
DOI: 10.1038/ncb1575
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-dependent anion channels are dispensable for mitochondrial-dependent cell death

Abstract: Voltage-dependent anion channels (VDACs) have been implicated as essential mediators of mitochondrial-dependent cell death by functioning as a channel-forming unit within the mitochondrial permeability transition (MPT) pore and the target of Bcl-2 family members. Here we report the effects of deletion of the 3 mammalian Vdac genes on mitochondrial-dependent cell death. Mitochondria from Vdac1-, Vdac3-, and Vdac1/Vdac3-null mice exhibited a Ca 2+ and oxidative stress-induced MPT that was indistinguishable from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
631
2
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 847 publications
(657 citation statements)
references
References 38 publications
14
631
2
10
Order By: Relevance
“…An adjuvant role of the voltage-dependent anion channels in membrane permeabilization has also been reported [9,10]. Disruption of OMM leads to the release of cytochrome c, which forms the 'apoptosome' with caspase-9 and the apoptosis protease activating factor (APAF).…”
Section: Intrinsic Pathwaymentioning
confidence: 96%
“…An adjuvant role of the voltage-dependent anion channels in membrane permeabilization has also been reported [9,10]. Disruption of OMM leads to the release of cytochrome c, which forms the 'apoptosome' with caspase-9 and the apoptosis protease activating factor (APAF).…”
Section: Intrinsic Pathwaymentioning
confidence: 96%
“…This finding underlines the major role postulated for CyPD in the formation of the mPTP, and suggests a higher susceptibility to mPTP opening at an older age. Indeed, it was demonstrated that mPTP formation and apoptotic cell death could still occur in the absence of either ANT [57] or VDAC [58]. In contrast, overexpression of CyPD induced mitochondrial swelling and spontaneous cardiac apoptosis, whereas mice lacking cardiac CyPD were protected from ischemia/reperfusion-induced cell death [59].…”
Section: The Involvement Of Apoptosis In the Pathogenesis Of Sarcopeniamentioning
confidence: 99%
“…Many proteins were thought to form the core of the pore across the mitochondrial membrane but they have been successively ruled out by genetic modulation. This is the case for the voltage‐dependent anion channel (VDAC) and the translocator protein (TSPO) in the outer membrane (Baines, Kaiser, Sheiko, Craigen, & Molkentin, 2007; Kokoszka et al., 2004). Recent data propose a role for ATP synthase as the major component of a multiproteic complex (Bernardi, Rasola, Forte, & Lippe, 2015).…”
Section: Introductionmentioning
confidence: 99%